Contaminants in food chains of arctic ungulates: what have we learned from the Chernobyl accident? - Åhman, Birgitta (Rangifer, 1998)
The Chernobyl accidenr of 1986 caused radioactive contamination of widespread areas of reindeer pasture in Scandinavia. Reindeer {Rangifer tarandus) are especially exposed to radioactive fallout due to their wintet diet, of which lichens are an important part. Much knowledge about the transfer of radiocaesium to reindeer, and via reindeer meat to man, was accumulated by intense scientific investigations, undertaken during the 1960s and 1970s, following nuclear weapons testing. Various ways to reduce the transfer of radiocaesium to animals and humans were also developed during this time. Much of the older knowledge proved to be of great value in the attempts to determine potential consequences of the Chernobyl accident and to suggest possible ways to ameliorate the effects of contamination. After Chernobyl, not only did reindeer prove to be a problem; many other food products originating ftom natural and semi-natural ecosystems were found to accumulate significant amounts of radiocaesium. Intense scientific work has produced new knowledge about the role of ungulates in the transfer of nutrients and contaminants within these systems. Different measures, like providing uncontaminated feed, use of caesium binders, altering the time of slaughter have been used with good results to minimize the transfer of radiocaesium to animals grazing natural pastures. The high cost of countermeasures has enforced consideration of cost against risk, which may also be of general interest with respect to other forms of pollution. Information, introduction of countermeasures and so forth would be more efficient in case a similar accident were to happen again. The Chernobyl accident is an obvious example of how human failures when dealing with a modern technical system can have global consequences and also be a potential threat to what we like to think of as the unspoiled wilderness of the Arctic.